Role of syn-eruptive plagioclase disequilibrium crystallization in basaltic magma ascent dynamics - G. La Spina (Nature Portfolio, 2016)
The quantification of timing for crystallization and exsolution processes are fundamental to our understanding of basaltic magma ascent dynamics. Here, the authors constrain timings to show that plagioclase reaches equilibrium in 1-2 hours, whereas ascent times were <1 hour.